Precedents, development and toponymic imprint of the “estación del Mármol” project (Hinojosa del Duque, Córdoba) (TST. Transportes, Servicios y Telecomunicaciones, 2025)
In the northern part of the province of Córdoba, the exploitation of coal and lead shaped a railway network that hardly met the needs of the significant agricultural and livestock municipality of Hinojosa del Duque. To address this situation, in 1904-1908 Hinojosa headed a formal proposal to construct a new railway line that did not attract the interest of railway companies. Since then, the municipality demanded the construction of a new station on the Almorchón-Belmez line, known as “estación del Mármol”. However, the project failed due to a lack of financial support during the periods of MZA (Madrid-Zaragoza-Alicante Railway Company) and later RENFE (Spanish National Railway Network). Paradoxically, confusion arising during the Spanish Civil War allowed the toponyms of "estación del Mármol" to persist in numerous publications and maps.
Keywords: mining; MZA; Los Pedroches; railway; RENFE; toponymy; Valle del Guadiato